2015
DOI: 10.1039/c5gc00430f
|View full text |Cite
|
Sign up to set email alerts
|

Supported gold nanoparticles as efficient and reusable heterogeneous catalyst for cycloisomerization reactions

Abstract: We report the utilization of a novel catalyst for cycloisomerizations. The novel catalyst system contains gold nanoparticles supported on Al-SBA15, which was prepared by the ball-milling process. We developed a greener methodology for synthesizing spiroindolines under heterogeneous conditions, using this novel class of supported gold nanoparticles in combination with microwave irradiation. The catalyst is highly reusable and selective. Cycloisomerization reaction yields ranged from good to excellent leading to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(27 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…[9] To furtheri nvesti- gate the role of water in this matter, the reaction was performed with and without the addition of water in batch under microwavei rradiation( MW), which can be seen in Scheme 2. We found that the presence of water results in an accelerated formation of spiroindoline 2h.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[9] To furtheri nvesti- gate the role of water in this matter, the reaction was performed with and without the addition of water in batch under microwavei rradiation( MW), which can be seen in Scheme 2. We found that the presence of water results in an accelerated formation of spiroindoline 2h.…”
Section: Resultsmentioning
confidence: 99%
“…[8] Recently,o ur group developed an ovelh eterogeneous gold catalyst, consisting of gold nanoparticles on an Al-SBA15 support,f or the cycloisomerization of Ugi-adducts. [9] Ther eactione nabled access to various spiroindolines and diazepino [1,2-b]indazoles.Am ajor advantage of the protocolw as the use of ethanol as as ustainable solvent in substitution for dichloromethane or other chlorinateds olvents, which are common for most gold-catalyzed reactions. [1] The scope of the reactionw as limitedw ith regard to the substitution pattern of the alkynes within the Ugi-adducts.M ores pecifically,a ni nternal alkyne bearing methyl, ethyl or para-methoxyphenyl groups,r esulted in prolonged reactiont imes under batch conditions, typicallyu sing catalyst loadings of 10 mol%a t8 08 8C.…”
Section: Introductionmentioning
confidence: 99%
“…Supported Au(0) nanoparticles (Au NPs) have been proven as excellent catalysts in cycloisomerization transformations, where the activation of sp ‐carbon π bonds (alkynes or allenes) on the low coordinated electrophilic Au atoms at the corners or edges of nanoparticles triggers intramolecular nucleophilic attack by carbon nucleophiles (Scheme ) . Thus, simple 1,6‐enynes, N ‐((1 H ‐indol‐3‐yl)methyl)propiolamides ( N ‐1,6‐enynes), aryl propargyl ethers, or ω‐alkynylfurans undergo cyclization in the presence of catalytic amounts of supported Au nanoparticles. In addition, the activation of an alkyne or allene by Au NPs may trigger inter or intramolecular nucleophilic attack by nitrogen, oxygen, or other nucleophiles.…”
Section: Methodsmentioning
confidence: 99%
“…[14] In 1997, Trost described the phosphine-catalyzed a-umpolung Michael reactiono fa lkyl esters with sulfonyla mine or phthalimide to achieve a-aminoc arbonyl compounds (Scheme 1d). [15] The reactionp roceeds through severali ntermediates, of which intermediate II could be trapped with different nucleophiles.With our enduring interesti ns piroindol(en)ines, [16] we planned to trap the intermediate II through an intramolecular nucleophilic attack of the C-3 position of the indole (Scheme 1e).Scheme1.Background on spiroindolenines framework.[a] P.Supporting information and the ORCID identification number(s) for the author(s) of this article can be found under: https://doi.…”
mentioning
confidence: 99%